USE OF AIRCRAFT FOR SITUATION MONITORING IN THE ARAL ZONE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses the use of unmanned aerial vehicles for monitoring the situation in the Aral zone.